The listening skill of autistic students in learning English through total physical response - Diana Fauzia Sari; Evriani Rotua Gea; Dian Fajrina (Universitas Syiah Kuala, 2021)
This study analyses how a teacher at SMPLB-CD YPAC (Foundation for Children with Disabilities), Banda Aceh, Indonesia, teaches English listening using the Total Physical Response (TPR) method to autistic students. In this method, a teacher instructed the students to act as modelled by the teacher. Students are considered to have good listening comprehension if they understood the teacher’s commands and imitated the act. This research is qualitative to describe the application of the TPR method in teaching English listening skills to autistic students. The sample for this study was four autistic students at the school under study. The data were collected by observing and documenting the English listening teaching-learning process in the classroom using the TPR method. The data were then analysed, focusing on the classroom dialogues directly related to using the TPR method to teach listening comprehension to autistic students. The results showed that the TPR method is suitable to teach students with autism to learn and understand new words. This was because they were asked to imitate the words verbally and in action repeatedly. The students could memorize the new vocabulary because it involved motor activities, which created a fun atmosphere in the classroom. Students were active in doing the actions and have no pressure to learn. The TPR method also contains elements of games which is able to raise a positive mood in autistic students.